Answer:
true!
Step-by-step explanation:
this is more of a statement then a question.
Answer:
the answer is B
Step-by-step explanation:
Answer:
we can use centeroid formula of a triangle
that is (x1+x2+x3)/3
hope that helps : )
Answer:
Step-by-step explanation:
Required to prove that:
Sin θ(Sec θ + Cosec θ)= tan θ+1
Steps:
Recall sec θ= 1/cos θ and cosec θ=1/sin θ
Substitution into the Left Hand Side gives:
Sin θ(Sec θ + Cosec θ)
= Sin θ(1/cos θ + 1/sinθ )
Expanding the Brackets
=sinθ/cos θ + sinθ/sinθ
=tanθ+1 which is the Right Hand Side as required.
Note that from trigonometry sinθ/cosθ = tan θ
Hello,
We have : (a + b)² = a² + 2ab + b²
4x² + 20x + 25 = (2x)² + 2 × 2x × 5 + 5² = (2x + 5)² → answer B
Here, we have a = 2x and b = 5 !